2015
DOI: 10.1002/14651858.cd007346.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Safety of topical corticosteroids in pregnancy

Abstract: This update adds more evidence showing no causal associations between maternal exposure to topical corticosteroids of all potencies and pregnancy outcomes including mode of delivery, congenital abnormalities, preterm delivery, foetal death, and low Apgar score, which is consistent with the previous version of this review. This update provides stratified analyses based on steroid potency; we found no association between maternal use of topical corticosteroids of any potency and an increase in adverse pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 56 publications
0
35
0
3
Order By: Relevance
“…Overall, the level of evidence was classified by the authors as 'very low' since all studies were observational, and variation observed in the results of the included studies was high. 48 In conclusion, several studies have examined the risk of TCS use in pregnancy, and overall, it has been deemed safe, although the use of very potent topical corticosteroids may be associated with low birthweight. There is an exception, though fluticasone propionate is the only TCS that is known not to be metabolized by the placenta and therefore should not be used in pregnant women.…”
Section: Menmentioning
confidence: 99%
“…Overall, the level of evidence was classified by the authors as 'very low' since all studies were observational, and variation observed in the results of the included studies was high. 48 In conclusion, several studies have examined the risk of TCS use in pregnancy, and overall, it has been deemed safe, although the use of very potent topical corticosteroids may be associated with low birthweight. There is an exception, though fluticasone propionate is the only TCS that is known not to be metabolized by the placenta and therefore should not be used in pregnant women.…”
Section: Menmentioning
confidence: 99%
“…Mid-to high-potency topical corticosteroids could be used once or twice a day as adjuvant therapy in localized form of disease (Serrano-Falcon & Serrano-Falcon, 2010). Several observational studies and metaanalyses asses the safety of topical corticosteroid use during pregnancy (Chi et al 2015;Chi, Wang, & Kirtschig, 2016). However, an increased risk of low birth weight was reported when exceeding 300 g of a potent or superpotent topical corticosteroids during the whole pregnancy (Chi, Wang, Mayon-White, & Wojnarowska, 2013).…”
Section: Discussion An D Con Cl Usion Smentioning
confidence: 99%
“…An updated Cochrane Review evaluated the effect of TCS use on pregnancy outcomes, with a total of 1 601 515 patients. Most studies found no causal associations between maternal exposure to TCS and adverse pregnancy outcomes.…”
Section: Treatment Of Atopic Eczemamentioning
confidence: 99%